Justiça e comprometimento acadêmico de alunos de pós-graduação stricto sensu em Ciências Contábeis de instituições de ensino superior brasileiras - Karla Luisa Costa Sabino (2023)
This study’s general objective was to analyze the relationship between academic commitment of stricto sensu graduate students in Accounting and their perception of justice. The research’s theoretical constructs were based on Pace (1958, 1963, 1979), Astin (1984), Homans (1961), Adams (1965), Rusbult et al. (1998), Colquitt (2001), Chory-Assad (2007), Human-Vogel and Rabe (2015), Simil (2016) and Sabino et al. (2019). Based on these, it was identified that academic commitment can be measured through a multidimensional model, formed by: i) the student’s satisfaction level in continue their studies; ii) the student’s investment to permanence and conclude their studies; iii) the student's quality of available alternatives beside studying; and, iii) the studies significance for the student, measured as the propensity to set goals. Similarly, the perception of justice could also be measured by a multidimensional model, formed by distributive justice (distribution of rewards), procedural justice (related to the procedures adopted by those who make decisions), interactional justice (linked to interpersonal relationships) and academic justice (associated with the relationships and rules inherent in the stricto sensu postgraduate environment). Based on this definition, 8 research hypotheses were drawn up, relating these dimensions to academic commitment. The methodological proceeding followed quantitative and qualitative approaches. For the quantitative approach, the sample gathered 308 stricto sensu graduate students in Accounting from 35 Brazilian institutions. For data collection, a questionnaire was used, consisting of 79 items divided into two scales: one for academic commitment and one for perception of justice. Additionally, 5 items collected sociodemographic information (age, gender, marital status, income, and academic term), and 9 items focused on sociodemographic characteristics. To analyze the questionnaire responses, factor analysis was employed to determine the scores generated by the two scales, and multiple regression was used to test the hypotheses and sociodemographic variables. Quantitative analyzes indicated that of the 8 hypotheses tested, 6 were not rejected, indicating that the level of satisfaction, quality of alternatives, significance and size of investment, as well as the dimensions of interactional justice and the justice of the stricto postgraduate environment sensu influence academic commitment. Among the sociodemographic variables, only the period and marital status variables were statistically significant, indicating that married students have less academic commitment and that students who are in more advanced periods have a greater academic commitment. For the qualitative approach, 11 students were interviewed, using a semi-structured interview script. The qualitative analysis followed the discourse analysis model, having as corpus the reports of this group of students. The results showed that the perception of justice in the stricto sensu postgraduate environment influences the students' academic commitment, especially the aspects linked to the relationship between professors and students. This research contributes to the consolidation of the Theory of Equity, with the validation of a new dimension of justice in the stricto sensu postgraduate environment, and broadens the discussion and understanding of the factors that influence the academic commitment of students, also contributing to the improvement of pedagogical practices and conduct.